State of Research on the History of the Lubrański Academy - Nowicki, Michał (Biuletyn Historii Wychowania, 2018)
The article tells about historiography of a famous Polish school – Collegium Lubranscianum (English Lubrański Academy), which originated in 1519 and existed until 1780. The whole text divided into few groups, showing the position of Lubranscianum in the interpretations of historians and the lack of research allowing recognition of some aspects of Lubranscianum history, such as the educational process of young people in the school, including the methods and handbooks, or, in general, the history of the school in the seventieth and eighteenth century. It is stressed that only few works bring new knowledge into out problem and most of the historiography is based on previously published works.